Pemanfaatan Potensi Lahan Rawa untuk Pengembangan Tanaman Kelapa Sawit di Lingkungan Universitas Sriwijaya - Satria Jaya Priatna; M. Bambang Prayitno; Bakri Bakri (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Priatna SJ, Prayitno MB, Bakri B. 2020. Utilization of wet land potential for plant development oil palm in sriwijaya university. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of Sriwijaya University asset is a very wide land at Inderalaya. The area is estimated to be 712 hectares, but it is still not fully utilized because some of its land is wetlands. With this potential, a study was conducted to evaluate the suitability level of oil palm in wetlands within the Sriwijaya University at Inderalaya. The survey activities are classified as detailed soil surveys (1: 10.000 scale). The location of the soil sample are determined with purposive sampling method with 40 cm of boring depth from the ground surface. Evaluation of land capability is done by matching method between the land characteristics with the optimal conditions for oil palm growth. The results showed that the actual suitability class on the land in general was classified as S3 (marginally suitable) with several inhibiting factors in the form of inundated land conditions, pH values and CEC that were not supportive and also minimal nutrient availability. Land quality improvement activities can be carried out on land to increase the suitability class to S1 (very suitable).